If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(c + -5) = 4 Reorder the terms: 6(-5 + c) = 4 (-5 * 6 + c * 6) = 4 (-30 + 6c) = 4 Solving -30 + 6c = 4 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '30' to each side of the equation. -30 + 30 + 6c = 4 + 30 Combine like terms: -30 + 30 = 0 0 + 6c = 4 + 30 6c = 4 + 30 Combine like terms: 4 + 30 = 34 6c = 34 Divide each side by '6'. c = 5.666666667 Simplifying c = 5.666666667
| x+4+6=6+3x | | 6(x+3)-5=19-4x-6+10x | | 2(x+3)=7x+5-5x+1 | | x+4+5x=6+3x | | 21=-7+z | | 7y^2-8y+3=0 | | 1.7*0.8=x | | a-2=27 | | 78(x+89)+11x=89x+2149 | | -x+4+5x=28 | | 1.2y^3-6y=0 | | (3x+2)(x+1)=3x*2+17 | | 6m-5=1 | | 2X^2=6x+4 | | -27+6(n-30)=3(n+5) | | 60+5x+15+5x=10 | | 41-29x=5-8x | | 5.5+13w=41.5 | | 1+x-6x=-44 | | 3x-7+5x=19 | | 8(w-8)=-6w-36 | | -1+9(x-2)=16x+4-7x | | 9x-11=6x-16 | | 5.5+13X=41.5 | | (1.4)2= | | 7b+3-4b=3-3b+4 | | s=36+0.1s | | -3=6-x | | 16-47=7(x-1)-3 | | 27+6B=81 | | x-0.52=0.69 | | -8(x+6)=2x-56 |